The Generalization Error Bound for the Multiclass Analytical Center Classifier - Zeng Fanzi; Ma Xiaolong (The Scientific World Journal)
This paper presents the multiclass classifier based on analytical center of feasible space (MACM). This multiclass classifier is formulated as quadratic constrained linear optimization and does not need repeatedly constructing classifiers to separate a single class from all the others. Its generalization error upper bound is proved theoretically. The experiments on benchmark datasets validate the generalization performance of MACM.